Hoarding : what everyone needs to know - Steketee, Gail; Bratiotis, Christiana (What everyone needs to know., 2020)
"In 2013, the American Psychiatric Association determined that hoarding disorder (HD) is a diagnosable mental health condition. This disorder has been studied only in the past three decades, although information about this surprisingly common problem has been accumulating at a great rate in recent years. In fact, published papers about hoarding have increased from 3 during the first half of the 1990s to 319 in first half of the current decade (2010-2015). This increased rate of published research on hoarding has continued in the past few years. In Dr. Randy Frost and Dr. Tamara Hartl's seminal 1996 paper on the "compulsive hoarding" syndrome, the authors proposed an explanation as to why people hoarded objects in their homes. Remarkably, the information they provided and their explanation stand up well today, even after scores of studies have been conducted on the psychopathology and treatment of hoarding. No doubt this information will continue to be updated in the coming years, but it provides a sound basis for understanding this complex and very serious condition"--